2012
DOI: 10.1080/1331677x.2012.11517528
|View full text |Cite
|
Sign up to set email alerts
|

The Sensitivity Of Capital Services Index on Construction Price Indices

Abstract: Measuring capital is a challenging task due to numerous conceptual dilemmas and practical problems. In this paper, we focus on the production side of capital measurement where the reliable measurement of capital services is of vital importance for derived production measures, such as multifactor productivity. While there has been a lot of debate regarding the choice of expected rate of return, the choice of expected capital gain, and the treatment of taxes in the user cost estimation when estimating capital, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…One of the most recent studies showed that consumer price index has the highest impact on construction price index compared to other factors (such as GDP, basic interest rate, foreign exchange rate and total export and import) (Nguyen & Nguyen, 2020). Kodrič and Bregar (2012) in their research related to Slovenia showed that the compilation of construction price indices for the period 1995-2008, in the hypothetical scenario, could affect the growth path of consumer price index if productivity, profit rate and quality changes are used. Kargi (2013) on the case of Turkey for the period 2000-2012, confirmed that infrastructure predominantly affects the growth along with the public sector expenditure.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One of the most recent studies showed that consumer price index has the highest impact on construction price index compared to other factors (such as GDP, basic interest rate, foreign exchange rate and total export and import) (Nguyen & Nguyen, 2020). Kodrič and Bregar (2012) in their research related to Slovenia showed that the compilation of construction price indices for the period 1995-2008, in the hypothetical scenario, could affect the growth path of consumer price index if productivity, profit rate and quality changes are used. Kargi (2013) on the case of Turkey for the period 2000-2012, confirmed that infrastructure predominantly affects the growth along with the public sector expenditure.…”
Section: Literature Reviewmentioning
confidence: 99%